Inhibitor encapsulated, self-healable and cytocompatible chitosan multilayer coating on biodegradable Mg alloy: a pH-responsive design12. Issue 14 (23rd March 2016) - Jia, Zhaojun; Xiong, Pan; Shi, Yuying; Zhou, Wenhao; Cheng, Yan; Zheng, Yufeng; Xi, Tingfei; Wei, Shicheng
Abstract : Self-healable, pH-responsive coatings on biodegradable Mg–Ca alloy are prepared, which exhibit unique self-healing activity against biocorrosion and elicit good biocompatibility towards pre-osteoblastic MC3T3-E1 cells. Abstract : The design of functional biomaterials that respond intelligently to external stimuli has become a rapidly growing area with widespread interest. This work contributes to the development of a feedback-active anticorrosion system with intriguing self-healing ability to protect magnesium (Mg) from biocorrosion. The system was constituted by an inner micro/nano-porous, ceramic-like pre-coating developed readily from the substrate, and an outermost inhibitor (nanosized cerium (Ce) oxides) containing chitosan (CS) multilayers. Here, the pre-coating acted as both an "anchoring" and a "barrier" layer to acquire structural integrity and improved impedance, respectively. Green CS served as cargo for Ce to be entrapped, harnessing Ce–NH2 complexation chemistry. The coating barrier properties were evaluated by electrochemical impedance spectroscopy. The active corrosion inhibition was assessed by immersion degradation tests with respect to Mg 2+ release, pH alteration, crack development, and scanning Kelvin potential. To our delight, the coatings effectively protected the substrate from biocorrosion in vitro compared with bare alloys. Putatively, the pH-triggered formation of Ce oxide precipitation, along with the pH-buffering activity and movable swelling capacity of CS macromolecules, should have contributed to restraining the anodic activity and healing the cracks/defects dynamically. Furthermore, the coated substrate had the biocompatibility to elicit better attachment and growth of osteoblasts.